1997
DOI: 10.1021/om960991i
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous Oxide Mediated Oxygen Atom Insertion into a Ruthenium−Hydride Bond. Synthesis and Reactivity of the Monomeric Hydroxoruthenium Complex (DMPE)2Ru(H)(OH)

Abstract: of protic reagents to 1 results in the replacement of the OH group with several other ligands, including aryloxo, thiolato, siloxo, C-bound enolate, acetylide, and triphenylstannyl; more deep-seated changes take place when 1 reacts with p-tolualdehyde and hexafluoroacetone.We wish to report the first observation of oxygen atom transfer from N 2 O into a late transition metalhydrogen bond and the chemistry of the hydroxohydridoruthenium complex produced in this reaction.Many catalytic processes involve intermed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(19 citation statements)
references
References 37 publications
1
17
0
1
Order By: Relevance
“…Thus, the reaction mechanism is similar to that of the Baeyer ± Villiger reduction of ketones. [26c] Bergman et al demonstrated that ruthenium complexes capable of producing unsaturated species cleave the C À C bond in acetone [27] and hexafluoroacetone [28] (Scheme 8). Cleavage of the CÀC bond in cyclic aliphatic ketones with [Rh(PPh 3 ) 3 Cl] has been reported by Murakami, Ito et al Exclusive activation of the less substituted C À C bond a to a carbonyl group has been observed.…”
Section: Activation Of C à C Bonds Adjacent To a Carbonyl Groupmentioning
confidence: 99%
“…Thus, the reaction mechanism is similar to that of the Baeyer ± Villiger reduction of ketones. [26c] Bergman et al demonstrated that ruthenium complexes capable of producing unsaturated species cleave the C À C bond in acetone [27] and hexafluoroacetone [28] (Scheme 8). Cleavage of the CÀC bond in cyclic aliphatic ketones with [Rh(PPh 3 ) 3 Cl] has been reported by Murakami, Ito et al Exclusive activation of the less substituted C À C bond a to a carbonyl group has been observed.…”
Section: Activation Of C à C Bonds Adjacent To a Carbonyl Groupmentioning
confidence: 99%
“…As shown in Figure 5 (1) Methane has been formed with a H 2 C-H···Ru interaction. After dissociation of the resulting methane molecule, the methoxyl ligand smoothly binds to the metal center to form a Ru-OMe σ bond, thus giving methoxide intermediate IM1, [38,39] which is calculated to be 15.6 kcal mol -1 more stable in free energy than mono-acetylido complex B. (2) The Ru···O(Me) distance was computed to be as long as 4.135 Å, which results in the unstable intermediate.…”
Section: The Transformation From B To D In the Presence Of Methanolmentioning
confidence: 99%
“…Bergman and coworkers [195,196] demonstrated that N 2 O is capable of mediating O-atom insertion into a late metal-hydrogen bond, in this case to afford a hydroxy-Ru complex (Scheme 2.10).…”
Section: Oxo Transfer Reactionsmentioning
confidence: 99%